Characterization of melanin from Exophiala mesophila with the prospect of potential biotechnological applications - Medina-Armijo, Cristy; Yousef, Ibraheem; Berná, Antonio; Puerta, Anna; Esteve-Núñez, Abraham; Viñas, Marc; Prenafeta-Boldú, Francesc X. (Frontiers in Fungal Biology, 2024)
Introducion Fungal melanin is an underexplored natural biomaterial of great biotechnological interest in different areas. This study investigated the physical, chemical, electrochemical, and metal-binding properties of melanin extracted from the metallotolerant black fungus Exophiala mesophila strain IRTA-M2-F10. Materials and methods Specific inhibitory studies with tricyclazole and biochemical profiling of whole cells by synchrotron radiation-based Fourier-transform infrared spectral microscopy (SR-FTIRM) were performed. An optimized extraction protocol was implemented, and purified fungal melanin was characterized using an array of spectrophotometric techniques (UV-Vis, FTIR, and EPR) and by cyclic voltammetry (CV) experiments. The metal-binding capacity of melanin extracts was also assessed by using Cr(VI) as a model heavy metal. Results Inhibitory studies indicated that 1,8-dihydroxynaphthalene may be the main precursor molecule of E. mesophila melanin (DHN-melanin). The biochemical characterization of fungal melanin extracts were benchmarked against those from two melanins comprising the precursor molecule L-3,4-dihydroxiphenylalanine (DOPA-melanin): extracts from the ink of the cephalopod Sepia officinalis and DOPA-melanin synthesized in the laboratory. The CV results of melanin extracts incubated with and without cell suspensions of the electroconductive bacterium Geobacter sulfurreducens were indicative of novel semiquinone/hydroquinone redox transformations specific for each melanin type. These interactions may play an important role in cation exchange for the adsorption of metals and in microbial interspecies electron transfer processes. Discussion The obtained results provided further evidence for the DHN-nature of E. mesophila melanin. The FTIR profiling of melanin extracts exposed to Cr(VI), compared to unexposed melanin, resulted in useful information on the distinct surface-binding properties of fungal melanin. The parameters of the Langmuir and Freundlicht isotherms for the adsorption of Cr(VI) were determined and compared to bibliographic data. Altogether, the inherent properties of fungal melanin suggest its promising potential as a biomaterial for environmental applications.